Influnce Of Carbon Monoxide On The Rate Of Depletion Of NOx In The Ozonation Of the Humid Exhaust Gases. - Fernando, W.J.N.; Mohamed, Abdul Rahman; Bakar, M Zailani Abu
Reactions involved in the ozonation of NOx present in exhaust gases are discussed. Associated reactions of Carbon monoxide, which is usually present in the exhaust gases, are also presented with particular reference to the case when moisture is present.